Maternal and Neonatal Risk Factors for Developing Early Onset Newborn Sepsis (EONS) in a Tertiary Care Hospital in Bangladesh (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Background: Globally, sepsis is still one of the major causes of morbidity and mortality in neonates, in spite of recent advances in health care units.Objective: To identify maternal and neonatal risk factors for developing early onset newborn sepsis (EONS) in a tertiary care hospital in Bangladesh.Methods: This cross-sectional study was carried out in the Neonatology department of Mugda Medical College Hospital (MuMCH) between November 2021 to April 2022 among the neonates who had clinical features of sepsis developed within 72 hours of postnatal age. After taking informed written consent from the parents the clinical profile and risk factors (both maternal and neonatal) were noted in a preformed data collection sheet. Blood for septic screening and C/S were done to confirm the diagnosis.Results: Majority (90.0%) newborns had maternal risk factors of sepsis whereas 6(10.0%) had not any maternal risk factors of sepsis. Mothers of majority (80.0%) newborns with sepsis had PROM>18 hours. One third had UTI/ lower abdominal pain/ fever within last 2 weeks of delivery. In more than half (56.7%) of the newborn septic cases their mothers had prolonged labour. More than half (58.2%) newborns belonged to gestational age less than 37 completed weeks. About two third (66.7%) newborns belonged to birth weight less than 2500 gm. Almost one third (30.0%) newborns had prelacteal feeding. More than two third (70.0%) newborns were given 7.1% chlorohexidin. Six (10.0%) newborns required resuscitation by bag mask at birth.Conclusion: For newborn sepsis maternal risk factors PROM>18 hours, prolonged labour, P/ V examination more than 3 times were more common. Neonatal risk factors include prematurity, low birth weight, prelacteal feeding.Bangladesh J Obstet Gynaecol, 2022; Vol. 37(2): 132-138